PENERAPAN TEORI BELAJAR HUMANISTIK PADA PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Rudi Prasetyo; Oktaviani Adhi Suciptaningsih (Jurnal Ilmiah Global Education, 2022)
This study aims to describe the application of humanistic learning theory through differentiation learning in elementary schools. The method used in this study is the literature review method where the data comes from various sources of articles in electronic journals. The data collection technique used in this research is documentation. Furthermore, the data analysis technique used in this research is content analysis. The results of this study attempt to illustrate that differentiated learning is learning designed by the teacher to facilitate students in building their knowledge in the process of changing behavior that embodies the diversity of characteristics, interests, motivations of students. Humanistic learning theory is a theory that helps students to enjoy learning about subject matter. Humanistic learning theory can be used to implement differentiated learning in elementary schools. Humanistic learning theory emphasizes the activities of guiding, developing and directing the basic potential of students both in terms of cognitive, affective and psychomotor